PERSEPSI MASYARAKAT TERHADAP PERBANKAN SYARIAH DI KABUPATEN SUMENEP - Hermanto, Bambang; Syahril, Syahril (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
Research on Community Perceptions of Sharia Banking in Sumenep Regency. Islamic banking implements an interest-free system that aims to create justice, social and economic well-being and protect people's property rights. The purpose of this study is to determine public perceptions of Islamic banking in Sumenep district, with qualitative research methods by describing systematically, factually and accurately about people's perceptions of Islamic banking, by observing, interviewing directly and in depth and documenting it. Whereas the key informants of religious leaders / community leaders who will be interviewed in this study use the method of purposive selection. Sharia Banking in Sumenep Regency is a bank that operates not relying on interest but on the basis of profit sharing in accordance with Islamic Sharia. Sharia Bank is a form of market demand that requires a financial institution with a halal banking system and complies with sharia principles even though it has not been said to be 100% sharia or kaffa.